مدى وجود أعراض مرض متلازمة مبانى المکتبات على أخصائى مکتبات مصر العامة وأثر ذلک على سیر العمل :دراسة میدانیة - Mohamed Mohamed (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of this research is to find out the views of Egyptian librariesspecialists about the internal environment of their libraries, and to know thesymptoms of the disease they suffer from, and to make sure that the symptomsthey suffer from is due to "disease of building disease syndrome" and not forother reasons and also aims to know the extent The effect of "structuralsyndrome" on the functioning of the libraries under study and the extent ofawareness among the specialists in the libraries of Egypt in general, "disease ofbuilding disease syndrome," and the most important results of the study that23.79% of the total specialists in the system of public libraries of Egypt sufferedfrom the symptoms associated with the building, while 76.20% of all specialistsThe general library system in Egypt did not suffer from the symptoms associatedwith the building, and 89.83% of the total library specialists who suffered from thesymptoms of the study confirmed that these symptoms actually symptoms oflibrary syndrome, and that the symptoms of the syndrome of buildings negativelyaffected the efficiency of working libraries